Control químico de Pyricularia Grisea sacc.en el cultivo de arroz (oryza sativa l.) desarrollado en la Estación Experimental Agraria – El Porvenir– INIA – San Martín - Montilla Perez, Lindsay (2011)
This research was conducted at the Agricultural Experimental Station "El Porvenir" - INIA - Juan Guerra, with the aim of evaluating the efficiency of 7 commercial fungicides for control of Pyricularia grisea in rice (Oryza sativa L) same time and so do the cost benefit of each treatment, seeking to demonstrate the profitability of crop production. Similarly, the experiment design was adapted to a completely randomized block with eleven treatments and four replications. Before beginning the work was carried out soil analysis, the work was to perform the following activities: preparation of the seedbed bed where he made the first application, the broadcast seed at 150 g/m2, a field transplant definitive planting distance of 0.20 X 0.25 m. for all treatments. We did a second application at the beginning of tasseling and a third to 25% flowering. Intermittent irrigation is used and periodic flooding in times required, just the weather data were recorded in the area. Assessments made during the period of the crop in terms of production, indicated that the treatments VERTICAL + PROTEXIN, and VERTICAL VERTICAL VYDAN + STRONSIL are those which gave better yields in grain, just as the economic analysis indicates that higher returns had with the treatments in question, having the highest performance with VERTICAL + PROTEXIN treatment and therefore greater profitability. Regarding the incidence of Pyricularia grisea in the first application and treatment STRONSIL VERTICAL + PHORTIFY obtained the lowest percentage of leaf area affected for the second application processing and STRONSIL + PROTEXIN STRONSIL also indicated the lowest% of leaf area affected, and in the third application the STRONSIL followed VERTICAL + PROTEXIN, VERTICAL + PROTEXIN STRONSIL and were the least affected by Pyricularia grisea Sacc.